Risk factors for iron deficiency anemia in children under one year of age - Gongora-Ávila, Cesar Ramón (2021)
Objective: to identify risk factors for iron deficiency anemia in children under one year of age belonging to the Teaching Polyclinic "November 7" of the Majibacoa municipality during the year 2020.Methods: observational, descriptive, cross-sectional study in infants under one year of age with iron deficiency anemia belonging to the Teaching Polyclinic "7 de Noviembre" of the Majibacoa municipality during 2020. The universe consisted of 42 children under one year of age with iron deficiency anemia ; all of these were worked on. The variables were analyzed: age, sex, intensity of anemia, biological risk factors, and social and cultural risk factors.Results: 61,9 % were female; For its part, the age most represented was less than 6 months in both sexes, although it was more observed in females (33,3 %). 61,9 % had mild anemia. 69,0 % of mothers with gestational anemia, their children presented iron deficiency anemia; On the other hand, 47,6 % of children under one year of age had a history of abandoning exclusive breastfeeding. Conclusions: the antecedent of anemia during pregnancy, low birth weight, incorrect ablactation and abandonment of exclusive breastfeeding are the main risk factors at the origin of iron deficiency anemia in children under one year of age.